Microbial diversity, culture conditions, and application effect of YSJ: A composite microbial system for degradation of Yanshan ginger branches and leaves. - Wenhao Chen; Juan Li; Huawei Yuan; Ling You; Tao Wang; Zongjin Cao (PLoS ONE, 2022)
Background Yanshan ginger (Alpinia zerumbet) is a perennial herb used as a medicine and spice, and is beneficial for soil and water conservation in karst areas. Given the widespread utilization of Yanshan ginger in China and continuing expansion of the planting area, disposal of waste materials is problematic. The branches and leaves of Yanshan ginger contain a variety of potent antibacterial compounds, such as volatile oils, phenols, and diterpenoids, which hinder their rapid degradation by microorganisms. In this study, we screened and constructed a composite microbial system to provide a technical reference for production of organic fertilizer from the branches and leaves of Yanshan ginger. Methods A composite microbial system, "YanShan Jun" (YSJ), was developed by screening for efficient detoxification and degradation of the branches and leaves of Yanshan ginger. High-throughput sequencing technology was used to investigate the stability and diversity of YSJ subcultures. The culture conditions for YSJ were optimized by sequential single-factor experiments and response surface analysis. Yanshan ginger leaves and branches were inoculated with YSJ to study its effects on composting efficiency. Results The microbial composition of YSJ was stable and rich in diversity through continuous subculture. Through response surface analysis, the optimized culture conditions for YSJ were determined as follows: peptone 8.0 g/L, sodium chloride 9.0 g/L, calcium carbonate 5.2 g/L, yeast powder 1.6 g/L, cultivation temperature 56.1°C, and culture duration 6 d. Under these conditions, the degradation rate of Yanshan ginger was 58.32%, which was 14.22% higher than that before optimization. The ability of YSJ to degrade the antibacterial compounds of ginger after optimization was significantly enhanced. Inoculation of Yanshan ginger compost with YSJ increased the fermentation temperature, prolonged the high-temperature period, and reduced the water content and pH of the compost in the early stage. Conclusions Inoculation of plant compost with YSJ bacteria improves the nutritional environment of the compost, promotes the composting reaction, promotes the rapid formation of a strong indigenous microflora, forms a beneficial microecological environment, and increases the composting efficiency. This study provides a theoretical basis for practical application of YSJ for organic fertilizer production from Yanshan ginger.